Procedure for unfair dismissal claims in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis, 2009)
What happens when an employee loses his job or is unfairly dismissed? Procedure for Unfair Dismissal Claims in Malaysia is your A to Z guide on an important aspect of industrial law, namely, the procedure for unfair dismissal claims in the Malaysian context.